Physiological and Biochemical Aspects of Silicon-Mediated Resistance in Maize against Maydis Leaf Blight - Luis Felipe Lata-Tenesaca; Marcos José Barbosa Oliveira; Aline Vieira Barros; Bárbara Bezerra Menezes Picanço; Fabrício Ávila Rodrigues (Plants, 2024)
Maydis leaf blight (MLB), caused by the necrotrophic fungus Bipolaris maydis, has caused considerable yield losses in maize production. The hypothesis that maize plants with higher foliar silicon (Si) concentration can be more resistant against MLB was investigated in this study. This goal was achieved through an in-depth analysis of the photosynthetic apparatus (parameters of leaf gas exchange chlorophyll (Chl) a fluorescence and photosynthetic pigments) changes in activities of defense and antioxidative enzymes in leaves of maize plants with (+Si; 2 mM) and without (−Si; 0 mM) Si supplied, as well as challenged and not with B. maydis. The +Si plants showed reduced MLB symptoms (smaller lesions and lower disease severity) due to higher foliar Si concentration and less production of malondialdehyde, hydrogen peroxide, and radical anion superoxide compared to −Si plants. Higher values for leaf gas exchange (rate of net CO2 assimilation, stomatal conductance to water vapor, and transpiration rate) and Chl a fluorescence (variable-to-maximum Chl a fluorescence ratio, photochemical yield, and yield for dissipation by downregulation) parameters along with preserved pool of chlorophyll a+b and carotenoids were noticed for infected +Si plants compared to infected −Si plants. Activities of defense (chitinase, β-1,3-glucanase, phenylalanine ammonia-lyase, polyphenoloxidase, peroxidase, and lipoxygenase) and antioxidative (ascorbate peroxidase, catalase, superoxide dismutase, and glutathione reductase) enzymes were higher for infected +Si plants compared to infected −Si plants. Collectively, this study highlights the importance of using Si to boost maize resistance against MLB considering the more operative defense reactions and the robustness of the antioxidative metabolism of plants along with the preservation of their photosynthetic apparatus.